2021
DOI: 10.31246/mjn-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of stunting during the complementary feeding period 6-23 months in the Philippines

Abstract: Introduction: Stunting persists as a public health problem in the Philippines, affecting 30% of under-five children. This study aimed to identify the drivers of stunting in young Filipino children aged 6-23 months. Methods: Data were extracted from the cross-sectional Updating Survey conducted in 2015 by the Food and Nutrition Research Institute of the Department of Science and Technology (FNRI-DOST). Potential predictors of stunting, which were categorised into childrelated characteristics, feeding practices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The findings of a metaanalysis conducted in Bangladesh (Islam et al, 2020) reported that initiation of complementary feeding at or after seven months of age increased the risk of stunting by 1.23 times. This is also consistent with findings in the Philippines where untimely introduction of complementary foods (either too early or too late) increased the child's odds of being stunted by almost twice and of being severely stunted by more than four times (Guirindola, et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The findings of a metaanalysis conducted in Bangladesh (Islam et al, 2020) reported that initiation of complementary feeding at or after seven months of age increased the risk of stunting by 1.23 times. This is also consistent with findings in the Philippines where untimely introduction of complementary foods (either too early or too late) increased the child's odds of being stunted by almost twice and of being severely stunted by more than four times (Guirindola, et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Based on the reported measures of effect, age of child (at 12-23 months or annually) ( 27 , 33 ) , maternal education (≤9 years or only primary or secondary) ( 16 , 34 ) , low birth weight ( 27 ) , and short maternal stature (<151 cm) ( 27 , 34 ) are the predictors with the largest relative ratio, which increases the risk of stunting in Southeast Asian countries by up to two times. Then, regarding the odds of stunting in children aged 0-24 months, the odds increase up to five times in children who are male (at six months; aOR 9.20, at 12 months; aOR 5.66) ( 37 ) , have low birth weight (<2500 gr) ( 37 ) , are born prematurely (aOR 5.10) ( 17 ) , have short parental height (mother <145 cm and father <161.9 cm; aOR 5.93) ( 14 ) , have unemployed mothers (aOR 8.40) ( 15 ) or whose mother work as farmer/breeder (aOR 11.74) ( 15 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Gender, age, and birth weight of the child are predictors with the most supporting studies. However, specifically the age and gender of the child, due to their nature, this predictor which has also been shown to increase the risk of stunting up to three times (RR 3.04) and 99% (RR 1.99) respectively ( 27 ) , cannot be modified directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations